Cervical Cancer - de la Garza-Salazar, Jaime G.; Morales-Vásquez, Flavia; Meneses-Garcia, Abelardo (Springer International Publishing : Imprint: Springer, 2017)
This book provides readers with a thorough review on cervical cancer, treatment guidelines and emerging therapies available for the disease. It reviews the epidemiology clinical features, diagnosis, and medical management of cervical cancer. Given the increasing need for preventive strategies, treatment optimization with collaborative and integrative work, this book improves the actual and integral knowledge in this neoplasm. Given the high prevalence of this disease in Latin America, this is an important text for clinicians in this region. This book outlines the state of the art in cervical cancer treatments and is an indispensable companion for oncologists, gynecologists, surgeons and medical students.
Keywords: Medicine.; Gynecology.; Radiotherapy.; Oncology.; Pathology.; Epidemiology.; elektronické knihy; electronic books